Preliminary investigations on an enzyme immobilized optical biosensor for arsenite detection - Teoh, W. K. (Penerbit UTM Press, 2016)
Arsenite is an inorganic form of arsenic that poses hazardous effect to human. It is a common environmental heavy metal contaminant ubiquitously found in water and groundwater. In this study, an optical biosensor for arsenite determination was developed by immobilization of crude arsenite oxidase (Aio) extracted from recombinant E. coli, in chitosan solution coated on triacetyl-cellulose membrane employing DCPIP as colour indicator. The arsenite oxidase (Aio) was successfully expressed and extracted from recombinant E. coli strain BL21 (DE3). The protein concentration and specific activity of the crude arsenite oxidase were determined. Expression of Aio was confirmed by SDS-PAGE. The crude Aio was also successfully immobilized in chitosan and coated on triacetyl cellulose membrane. The response time and dynamic range of the optical biosensor were optimized. The response time of the developed biosensor was 15 minutes. The amount of DCPIP reduced (ΔA) was inversely proportional to the arsenite concentration. Standard calibration curve for arsenite detection was achieved within the range of arsenite concentration from 25 μM to 200 μM. The maximum detection limit was determined to be 250 μM arsenite.